Gastric Carcinoid with Hypergastrinemia: Report of Three Cases - Katsuyoshi Furumoto; Hidenobu Kojima; Masayuki Okuno; Hiroaki Fuji; Rei Mizuno; Tomohiko Mori; Daisuke Ito; Masafumi Kogire (Case Reports in Medicine)
We report 3 cases of gastric carcinoids with hypergastrinemia. Case 1: A 60-year-old man had a 2 cm carcinoid of the stomach and underwent partial resection. Involvement of the muscularis propria and lymph nodes metastasis were observed microscopically. Follow-up gastroscopy revealed another carcinoid lesion and total gastrectomy was performed. Case 2: A 67-year-old woman with multiple carcinoids of the entire stomach underwent antrectomy. No growth of residual tumors has been detected so far. Case 3: A 61-year-old man had a tumor near the esophagogastric junction and underwent total gastrectomy. Carcinoid component was diffusely intermingled with adenocarcinoma in the tumor and invaded into the subserosa. In all 3 cases, the serum gastrin level was high and atrophic gastritis was microscopically observed. Carcinoid tumor in Case 3 was different from those in Cases 1 and 2 and interestingly, gastric carcinoid with hypergastrinemia showed various types of appearance.